Implementation of the Jaccard Method in the WhatsApp Messenger Cyberbullying Investigation Analysis Using a Framework National Institute of Standards and Technology - Panggah Widiandana; Imam Riadi; Sunardi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The development of information technology is increasingly showing a great influence on human life. Based on the survey, it was stated that every year the users of the WhatsApp application grew very rapidly in 2015, 900 million users and in March 2020, it increased to 2000 million users. The data is straight-line with the increasing crime rate, one of which is cyberbullying which always increases every year. The purpose of research that has been carried out is to add references for investigators in conducting, including cases of cyberbullying. The National Institute of Standards and Technology (NIST) method is used to make it easier for researchers to conduct digital forensics on the evidence that has been obtained. The Jaccard method is used to identify evidence that has been obtained to obtain digital evidence to prove that cyberbullying has occurred. The results of research that have been done prove that the NIST method can simplify the process, in cyberbullying identity starting from the lifting of evidence to the reporting stage of evidence. The similarity jaccard method is able to identify cyberbullying with different levels, with the highest value of jaccard which is 0.21 (21%), and the lowest value obtained from a value of 0 (0%). The NIST method and the cyberbullying method can make it easier for investigators in cyberbullying cases.